БИР МӘРТЕЛИК ПАРОЛЬ ТИЙКАРЫНДА БИР БАҒДАРЛЫ АУТЕНТИФИКАЦИЯ ПРОТОКОЛЛАРЫНЫҢ АНАЛИЗИ - Арзиева, Ж.Т.; Калмуратова, С.М. (FAN va JAMIYAT, 2021)
The article deals with the state presented the analysis of protocols of single authentication on the basis of single passwords. A comparative analysis is presented OTP transmission methods in autnentification methods based on one-time passwords.